PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TEKNIK KELILING KELOMPOK UNTUK MENINGKATKAN HASIL BELAJAR PKN SISWA KELAS IV SD Negeri 006 KUALA LAHANG - Aguslim . (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2018)
The purpose of this research is to improve the students output of PKn subject class IV SD Negeri 006 Kuala Lahang. The sample which is obtained are 31 students of class IV SD Negeri 006 Kuala Lahang. Kind of the research is classrom action research. The data is obtained through: 1) students output test; 2) observation form of learning activity; and 3) the portofolio of group work output. The result of analyzing data indicated the average of students score is 62,32. In cycle 1 increased to 73,48, then in cycle 2 increased to 81,81. Based on this research, it can be concluded that an increased in students output through round-group technique of cooperative learning method